In-dept review on adherence to therapeutic regimen and well-being among patients with type II diabetes mellitus - Gloria S. E. Coyoca; Hanna C. P. Bejarasco; Veron G. T. Dalumbar; Eldon S. Mendoza (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Diabetes Mellitus or diabetes is an aggregation of metabolic diseases distinguished as a condition occurring when the body can’t utilize glucose from the foods eaten. In 2011, 366 million were diagnosed with diabetes mellitus with 4.6 million deaths and 50% among which are undiagnosed. According to the International Diabetes Federation in 2011, diabetes is expected to rise by about 552 million by the year 2030. Patient nonadherence can be a pervasive threat to health and well-being and carries an appreciable economic burden as well, yet, only few studies have been conducted to examine the relationship between adherence to therapeutic regimen and well-being among type 2 diabetic individuals The main intention of this study is to provide an in–depth review of the relationship between the adherence to therapeutic regimenand well–being among type 2 diabetic individuals in Iligan City. Descriptive Correlational design was utilized to describe the relationship between the variables under investigation. Modified standardized questionnaireswere given to 133 respondents who were chosen using a simple random sampling. Results showed that among the therapeutic regimen adherence investigated, most of the respondents have an average level of adherence to diet compared to medication, exercise, and stress reduction techniques in which their level of adherence scored good. For their well–being status, only mental scored good, while physical, emotional and spiritual scored average. Furthermore, findings showed a significant inverse relationship between age ofrespondents and their level of adherence to diet, the respondents’ work status and their level of adherence to diet and stress reduction techniques. Positive significant relationship was found between the respondents’ educational attainment and their level of adherence to therapeutic regimen, economic status and medication adherence, and educational attainment and mental well–being. Therefore, therapeutic regimen adherence was found to have a positive impact on the well–being of the respondents. Collaborative team consisting ofendocrinologists, nurses, nutritionists, dieticians, exercise physiologists, and spiritual leaders is highly recommended for the intensive management of diabetes patients, thus, improving adherence and well–being